Exploring the Trade Dynamics of Commercialized NTFPs in Gorkha, Nepal - Tiwari, Aastha (International Research Journal of MMC, 2025)
The commercialization of NTFPs has begun to receive attention for its potential to improve rural livelihoods and generate export revenues. This study focuses on the collection and marketing of commercialized NTFPs from Gorkha district. Primary data were gathered, drawing data from fiscal years (2075-81) of export permit records from the Division Forest Office, Gorkha, through key informants and phone interviews. Descriptive analysis was employed, with graphs and charts prepared using MS Excel, and ArcGIS utilized for mapping the study area. Currently, 38 plant species of NTFPs were traded from the district, categorized into seven groups based on their commercial applications. Medicinal and Aromatic Plants (MAPs) dominate the sector, comprising 66% of the total trade volume, followed by wild foods and dyes. Over the past five fiscal years, Gorkha district traded a total of 180,510 kg of NTFPs, generating approximately Rs. 2,256,615 in revenue. The highest revenue was recorded in FY 2080-81, followed by FY 2078-79. Six species - Girardinia diversifolia, Swertia chirayita, Neopicrorhiza scrophulariiflora, Moringa Oleifera, Curculigo orchioides, and Nardostachys grandiflora are noted for their high value based on revenue collected, while Bergenia ciliata, Majitho, Setakchini, Allo, and Kalo Musali lead in terms of quantity traded. The collection and supply chain of NTFPs in Gorkha district involves community and local collectors gathering products from various villages, which are then aggregated at local depots, such as Macchikhola, Baluwa Bajar, Dodheni Bajar. To ensure legality and facilitate transport, NTFPs were verified and issued transport permits by the DFO, Gorkha. Subsequently, regional traders distribute these products to different districts and national markets. The study recommends establishing species-specific scientific trading regulations to optimize market opportunities. Adequate research and favorable resources should be allocated to explore other potentially commercially traded NTFPs. Commercialization of NTFPs in Gorkha district could contribute significantly to local economic development by generating income for rural communities, but to optimize market opportunities and ensure sustainable trade, species-specific scientific regulations and further research are essential. This would help enhance the efficiency of the supply chain, ensure the legality of the trade, and potentially expand the range of commercially traded NTFPs.